The Experience of Transitional Care for Non-Medically Complex Older Adults and Their Family Caregivers - Alexandros Georgiadis; Oonagh Corrigan (SAGE Publishing, 2017)
Transitional care research has mainly focused on the experiences of older adults with complex medical conditions. To date, few publications examine the experience of transitional care for non-medically complex older adults. In this article, we draw on and thematically analyze interview and audio-diary data collected at three hospitals in Eastern England, and we explore the experience of transitional care of 18 older adults and family caregivers. Participants reported mixed experiences when describing their care transitions, which indicated variations in care quality. To achieve independence and overcome the difficulties with care transitions, participants used a range of interrogative techniques, such as questioning and information seeking. We contend that the existing transitional care interventions are inappropriate to address the care needs of non-medically complex older adults and family caregivers. Implications for frontline health care staff and health services researchers are discussed.